Replacement renal therapy in the treatment of patients with a severe course of the new coronavirus infection - S. N. Аvdeykin; D. M. Kostin; A. V. Srednyakov; D. N. Kazakov; N. I. Matyushkov; I. N. Tyurin; D. N. Protsenko (Вестник анестезиологии и реаниматологии, 2021)
Objective: to study the use of RRT methods and their influence on the results of treatment of patients with severe COVID-19.Subjects and methods. We retrospectively analyzed the data of 283 patients with COVID-19 in the intensive care units of Moscow City Hospital no. 40 in 2020 who had received RRT as one of the treatment methods.Results. Frequency of RRT in COVID-19 patients in ICU of Moscow City Hospital no. 40 for 2020 made 5.7% (504 out of 8.711 patients treated in ICU received RRT). In 86% of cases, RRT was performed for renal indications. At the time of initiation of RRT, the studied groups did not differ according to SOFA score. The frequency of using dialysis units with high and low cut-off point in the groups of survived and deceased patients differed significantly. The surgery itself started at relatively the same time from the onset and statistically significantly earlier in the group of survivors from the beginning of tracheal intubation (4.9 ± 0.5 vs 6.8 ± 0.3 days, p = 0.0013). Against the background of ongoing therapy, overall severity of the state progressed in the group of deceased patients to 9.9 ± 0.2 SOFA scores, while in the group of survivors there was an improvement to 6.1 ± 0.4 scores.